(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Known for her confessional mode of writing, Kamla Das’ (1934-2009) poetry offers an aesthetic of resistance to the phallocentric codes and conventions. What sets her poetry apart from the other Indian women poets writing in English is the brutal honesty with which she handles the issue of women’s search for subjectivity and autonomy in the face of patriarchal prohibitions. Her choice of a free poetic mode instead of regular metrical form suits her tone of anger and protest resulting from the marginalization of women. Hlowever while hitting out at the deeply entrenched patriarchal prejudices, she does not forget her own femininity. Das’s individuality lies in evolving a new language of protest. The expression of resentment and hurt in her poetry takes various forms - right from light-hearted mockery of the oppressor to downright denunciation of the repressive social set up to trenchant poetic images to name just a few.